All-fiber Passively Mode-locked Femtosecond Laser Based on a Femtosecond Laser Inscribed 45° Tilted Fiber Grating - Huang, Zinan; Huang, Qianqian; Theodosiou, Antreas; Kalli, Kyriacos; Mou, Chengbo (My University, 2019)
A femtosecond erbium-doped fiber laser using a novel 45° tilted fiber grating fabricated by direct femtosecond laser inscription is experimentally demonstrated. The laser generates stable short pulses with pulse width of 752 fs at 1562 nm.
Keywords: Erbium-doped fiber laser; Nonlinear polarization rotation; Tilted fiber grating